Native-born-immigrant wage gap revisited: The role of market imperfections in Canada - Yigit Aydede; Atul A. Dar (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2022)
Most studies investigating the poor earnings performance of immigrants implicitly assume that human capital endowments determine actual earnings, and that immigrant-nativeborn wage gaps can be analyzed in terms of those earnings. In this study we claim that this assumption is not validated by evidence and that wage gaps should be analyzed by examining earning potentials rather than actual wages that are also influenced by market imperfections. We apply a two-tier stochastic wage frontier, which allows us to separate potential wage earnings from actual wage earnings and to identify how much of the observed wage gap between immigrant and native-born workers in Canada is attributable to departures from their potential wage earnings due to imperfect information on the demand and supply side of labour markets. Using the 2006 population census data, our results suggest that, although the ethnic background plays an important role in determining the observed wage, a significant part of the wage gap between immigrants and native-born workers is not driven by worker and employer imperfect information, but by differences in human capital endowments.
Keywords: J6; J15; J61; 330; Imperfect information in labour markets; returns to education; occupational mismatch; stochastic frontier